Major farm practice report in JM (Jabelosa-Marcon) and Saint Jude Brooding Farm - Gaditano, Felicisima A.; Peñeda, Genna
This study describes the observed operations management of JM (Jabelosa-Marcon) and Saint Jude Brooding Farm in Cebu.